Stress, shock, and adaptation in the twentieth century - Cantor, David, 1957-; Ramsden, Edmund (Rochester studies in medical history., 2014)
This edited volume explores the emergence of the stress concept and its ever-changing definitions; its uses in making novel linkages between disciplines such as ecology, physiology, psychology, psychiatry, public health, urban planning, architecture, and a range of social sciences; its application in a variety of sites such as the battlefield, workplace, clinic, hospital, and home; and the emergence of techniques of stress management in a variety of different socio-cultural and scientific locations. In short, this volume explores what happened when stress entered the discourse around modernity.